Microbial Fabricated Nanosystems: Applications in Drug Delivery and Targeting - Sachin, Kumar; Karn, Santosh Kumar (Frontiers in Chemistry, 2021)
The emergence of nanosystems for different biomedical and drug delivery applications has drawn the attention of researchers worldwide. The likeness of microorganisms including bacteria, yeast, algae, fungi and even viruses towards metals thereby finding applications in bioremediation, biomineralization and as a chelating agent is well known. Higher tolerance to toxic metals has opened up a plethora of microbial fabricated nanomaterials; their synthesis, characterization and applications have been well documented and reviewed. Further, these materials can also be used in theranostics i.e. both therapeutics as well as diagnostics as a single species due to their ability to get functionalized. This document attempts to focus particularly on the application of such microbially derived nanoformulations as a drug delivery and targeting agent. Besides metal-based nanoparticles, there is enough evidence wherein nanoparticles have been formulated using only the organic component of microorganism. Enzymes, peptides, polysaccharides, polyhydroxyalkanoate (PHA) are amongst the most used for guiding crystal growth and as a capping/reducing agent in the fabrication of nanoparticles. This has promulgated the idea of complete green chemistry biosynthesis of nano-organics that are most sought after in terms of their biocompatibility and bioavailability. An account of comparison between the nano-organic and nano-inorganic delivery vehicles has also been presented.